The impact of the Corona virus (Covid-19) pandemic on the air transport sector - Mechtar, Fatima; Chin, Khathir; Dhif, Abdelghani (Finance and Business Economies Review, 2021)
The current research paper aims to address the impact of the Coronavirus (Covid-19) pandemic upon the air transportation sector, by introducing the virus and the development of its spread.In addition; the study addresses the implications of the aviation sector, by analyzing its impact on passenger movement, air freight, and employment. The study concluded that the Coronavirus pandemic has a significant impact on another sector such as global tourism.This is due to the closure of airports and travel restrictions imposed by many governments, which led to paralyzing movement for travelers.